2009
DOI: 10.1183/09031936.00018909
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of T-cell and antigen presenting cell co-stimulatory genes in childhood IgE

Abstract: It is likely that multiple genes contribute to immunoglobulin (Ig)E production. Co-stimulatory molecules are crucial for the cross-talk between antigen presenting cells and T-lymphocytes which drives the IgE response.We evaluated gene–gene interactions of haplotype tagging polymorphisms in a pathway of 24 co-stimulatory genes in relation to serum IgE levels. We assessed this at ages 1–2 yrs and 6–8 yrs in 3,062 Dutch children from a pooled data set of three birth cohorts: PIAMA (Prevention and Incidence Asthma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…The MDR approach has been described previously [37][38][39] and applied in this cohort. [40][41][42] The TLR2 gene has been studied in relation to other TLRs and atopy development by MDR (Reijmerink et al, unpublished data, May 2010). A detailed description of the MDR method is included in the Online Repository at www.jacionline.org, ''MDR'' section.…”
Section: Methodsmentioning
confidence: 98%
“…The MDR approach has been described previously [37][38][39] and applied in this cohort. [40][41][42] The TLR2 gene has been studied in relation to other TLRs and atopy development by MDR (Reijmerink et al, unpublished data, May 2010). A detailed description of the MDR method is included in the Online Repository at www.jacionline.org, ''MDR'' section.…”
Section: Methodsmentioning
confidence: 98%
“…Recently a genome-wide association analysis identifies 10 single-nucleotide polymorphisms (SNPs) in non-coding regions of the B7x gene that are strongly associated with juvenile idiopathic arthritis (9). In addition, two SNPs in the B7x gene are significantly associated with increased serum IgE in children (10). Despite these recently discovered genetic data linking the B7x gene to different autoimmune diseases, it is unclear how B7x contributes to peripheral tolerance and autoimmunity.…”
Section: Introductionmentioning
confidence: 99%
“…[2], [4], [12], [15], [29], this study confirmed a significant association between CD28 SNPs and total IgE in asthmatics (minimum P  = 0.001, data not shown). Serum total IgE levels have been elucidated to be correlated with CD28, an important regulator of T-cell activation and subsequent IgE production [30], [31]. In this study, differences in the results between present and previous GWASs might be attributed to population and/or ethnic differences, limitation and mismatch of the tested SNP markers (albeit only SNPs in the C11orf30 - LRRC32 region were matched with those of this GWAS), and a diversity of clinical phenotypes among asthma patients.…”
Section: Discussionmentioning
confidence: 99%